1970
DOI: 10.4314/ejhs.v29i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow and Peripheral Blood Cells Toxicity of a Single 2.0 Gy Cobalt60 Ionizing Radiation: An Animal Model

Abstract: BACKGROUND: Bone marrow is extremely vulnerable to damage caused by radiation therapy. Hence, bone marrow suppression is an important side effect of radiotherapy. Effective use of radiotherapy is therefore compromised by radiation-related injuries.MATERIAL AND METHODS: Six Guinea-pigs were recruited for the study of which three were subjected to total body irradiation with Co60 while the other three served as controls. Bone marrow and peripheral blood samples were collected before and at days 9, 14 and 21, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The bone marrow is extremely vulnerable to damage caused by RT. In a previous study, a significant decrease in lymphocyte counts was observed on days 14 and 21 after whole-body irradiation in guinea pigs ( 28 ). This is an effect of total-body irradiation, and the distribution and dynamics of lymphocytes in the body must be considered.…”
Section: Discussionmentioning
confidence: 75%
“…The bone marrow is extremely vulnerable to damage caused by RT. In a previous study, a significant decrease in lymphocyte counts was observed on days 14 and 21 after whole-body irradiation in guinea pigs ( 28 ). This is an effect of total-body irradiation, and the distribution and dynamics of lymphocytes in the body must be considered.…”
Section: Discussionmentioning
confidence: 75%
“…IR affects hematopoietic tissues, and significantly reduces the number of neutrophils and platelets. The resulting decrease in the number of peripheral blood cells can cause sepsis, bleeding, anemia and, in some cases, death ( 126 ). Therefore, radiation therapeutics aim to promote the recovery of hematopoietic function.…”
Section: Strategies To Reduce Radiation Injurymentioning
confidence: 99%
“…Ionizing radiation promotes the suppression of immunity and subsequent bone marrow depression ( Figure 1B ) ( 115 ). Within first 24 hours after irradiation, active apoptotic death of hematopoietic cells results in monocytopenia ( 116 ).…”
Section: Effects Of Treatment On Circulating Monocytesmentioning
confidence: 99%